Collaborative Process in Developing Ketenger Tourism Village, Banyumas Regency - Rianandita 'Arsy Elkesaki; Retno Sunu Astuti; Dyah Lituhayu (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The involvement of three pillars in tourism management: government, community, and private sector. Collaboration between these three pillars is crucial for creating a sustainable tourism industry, providing economic benefits for local communities, and preserving culture and the environment. One tourism sector that attracts visitors is the Ketenger Tourism Village in Banyumas Regency. Ketenger Village holds a wealth of natural and cultural potential supported by the ability and capacity of the tourism village's institutions to manage this potential. The purpose of this study is to determine the collaboration process in the development of the Ketenger Tourism Village. This study uses a descriptive research method with a qualitative approach. Secondary data to support the research were obtained through data available in journals, articles, newspapers, or online news. The results show that the Collaborative Governance process, which includes five indicators, has not been optimally implemented, particularly in the aspects of commitment to the process and shared understanding. However, other indicators have been running well in accordance with the government's pattern in developing the region, which will have an impact on the progress of the Ketenger Tourism Village.